Legal and Social Protection for Street Vendors on Menteri Soepeno Street, Semarang City Post-Relocation: Perlindungan Hukum dan Sosial Terhadap Pedagang Kaki Lima Jalan Menteri Soepeno Kota Semarang Pasca Relokasi - Lailasari Ekaningsih (Universitas Negeri Semarang, 2012)
Semarang City Government relocation policy against cadger( PKL ) from street Pahlawan to street Menteri Soepeno will cause the pros and cons of the respective cadger. Cadger should Obtain legal and social protection of post-relocation to comfort, well - being and the smooth cadger trading business in a new location. The method used in this study is qualitative research and descriptive research with socio-Juridical approach. While the methods of data collection used in the study were interviews, observation and documentation. Validity of the processing of data using triangulation techniques. The method of the data analysis used in this study is the data collection, data reduction, the data displa, conclusion. Results and discussion of this study were (1) the underlying policy relocation of cadgerfrom street Pahlawan to street Menteri Soepenois in order to create a SETARA program using basic equivalents Regional Regulation No.11 Year 2000 concerning Regulation and Development cadgerand the Decree No. . 511.3/16 on the Determination of Land / Territory Location of cadger in the city of Semarang .( 2 ) pos -relocation of cadger in the Street Menteri Soepeno in fact have repressive and preventive legal protection. Then the result of the relocation of cadger do not get social optimum protection. Get merchandisers limited to trade land compensation in the form of shelter and amenities along with a license for each cadger selling but they do not get social assistance in the form of a guarantee of labor and capital. Suggestions from the research and discussion are (1) Instead of Semarang City Government through their policies in curbing cadger should give serious attention to post-relocation of cadger (2) Semarang City Government should also give special attention to the social and legal protection against post-relocation of cadger in order to further its survival to develop prosper in the post-relocation wefforts